The Role Of Physical Activity In The Prevention And Treatment Of Cardiovascular Disease, Obesity And Diabetes - Mariańska-Wiśniewka, Ilona; Jankowska, Natalia; Świerzyńska, Adrianna; Simlat, Aleksandra; Cieciora, Aleksandra; Szwaj, Angelika; Surowiec, Julia; Puszkiel, Tomasz; Kawiorska, Małgorzata; Cieciora, Mateusz (Quality in Sport, 2026)
Physical activity is one of the most important elements in the prevention and treatment of cardiovascular diseases, both in people already suffering from heart conditions and in healthy individuals. However, effective exercise recommendations must be based on solid scientific evidence and tailored to the individual needs of the patient. The appropriate amount of exercise and level of cardiorespiratory fitness, as well as the right choice of intensity and training structure, all play an important role here. With age, the risk of cardiovascular disease increases, especially in the presence of metabolic disorders such as obesity and diabetes, which further impair the functioning of the circulatory system. Therefore, understanding the relationship between aging, risk factors, and the body's response to physical activity is crucial for proper prevention. This study presents the most important principles of physical activity planning and the importance of lifestyle changes in reducing the risk of cardiovascular disease in older people and patients with metabolic diseases. The document also emphasizes the role of specialized training programs as an integral part of modern care for people with increased cardiovascular risk.